2022
DOI: 10.1590/1678-4685-gmb-2022-0137
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and function of the PSEUDO RESPONSE REGULATOR gene family in the plant circadian clock

Abstract: PSEUDO-RESPONSE PROTEINS (PRRs) are a gene family vital for the generation of rhythms by the circadian clock. Plants have circadian clocks, or circadian oscillators, to adapt to a rhythmic environment. The circadian clock system can be divided into three parts: the core oscillator, the input pathways, and the output pathways. The PRRs have a role in all three parts. These nuclear proteins have an N-terminal pseudo receiver domain and a C-terminal CONSTANS, CONSTANS-LIKE, and TOC1 (CCT) domain. The PRRs can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Our study showed that MtPRRs can be grouped into the PRR5/9 clade, PRR3/7 clade, and TOC1 clade, which is highly conserved in many species, such as Arabidopsis, rice, Brassica rapa, and rose [18,54,55]. According to the previous study, there are five members of clock PRR genes in Arabidopsis thaliana, Sorghum bicolour, and Oryza sativa, all including one TOC1/PRR1 member gene, two genes in the PRR5/9 clade, and two genes in the PRR3/7 clade [41,56]. However, seven PRR genes were shown in the Medicago truncatula genome, including two genes in the TOC1/PRR1 clade, three members in the PRR5/9 clade, and two PRR3/7 members.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our study showed that MtPRRs can be grouped into the PRR5/9 clade, PRR3/7 clade, and TOC1 clade, which is highly conserved in many species, such as Arabidopsis, rice, Brassica rapa, and rose [18,54,55]. According to the previous study, there are five members of clock PRR genes in Arabidopsis thaliana, Sorghum bicolour, and Oryza sativa, all including one TOC1/PRR1 member gene, two genes in the PRR5/9 clade, and two genes in the PRR3/7 clade [41,56]. However, seven PRR genes were shown in the Medicago truncatula genome, including two genes in the TOC1/PRR1 clade, three members in the PRR5/9 clade, and two PRR3/7 members.…”
Section: Discussionmentioning
confidence: 98%
“…However, seven PRR genes were shown in the Medicago truncatula genome, including two genes in the TOC1/PRR1 clade, three members in the PRR5/9 clade, and two PRR3/7 members. This is mainly because PRRs were expanded in M. truncatula during evolution, and the duplication event tends to happen in the TOC1/PRR1 clade and PRR5/9 clade, which is also seen in the PRR family of Populus trichocarpa and Vitis vinifera [56]. Like the PRR proteins in Arabidopsis, rice, sorghum, and other plants, the PRRs in M. truncatula are also nuclear-localized with an N-terminal PR domain followed by the C-terminal CCT motif, and the structure and location similarity imply their potential functional conservation in monocot and dicot species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoperiod insensitive genotypes of cannabis were found to contain a splice site mutation in CsPRR37. CsPRR37 is homologous to other PRR family genes within the PRR3/7 clade (Hotta et al, 2022), many of which have been confirmed as bona fide timekeepers such as PRR7 in Arabidopsis , and PRR37 in rice. CsPRR37 contains both PR and CCT domains which are signature features of pseudo-response regulators.…”
Section: Discussionmentioning
confidence: 99%